APLIKASI METODE ANALISIS HIRARKI PROSES (AHP) PADA MODEL PEMILIHAN MODA PERJALANAN KERJA - Kurniawan, Yahya; Hasanuddin, Akhmad; Wahyuni, Sri (FSTPT Indonesia, 2015)
There is a tendency to concentrate housing area in southern part of Jember territory. This demographic condition caused traffic congestion during the rush hour. The objectives of this research are for estimating the priority weights of mode election, estimating the form of modal election models, and analyzing the sensitivity of factors in election of mode. Based on AHP, the result showed that the safety factor is become the main priority (46%), then the second is cost (41%), the third is time (8%) and the last is comfortable (5%). Based on the various factors that give effect to mode election, it’s known that lyn is the lowest priority (7%), motor cycle is 48% and car is 45%. The sensitivity analysis result, it’s known that decreasing and increasing of priority for each criterion do not give any significant changing in the election of lyn as working trips alternative transportation mode.